Environmental impact and indigenous peoples: a bibliometric study of the scientific literature in scopus - Gallego, Tulio Andrés Clavijo; Garcés, Carlos Enrique Osorio; Castillo, Verenice Sánchez (Journal of Ecohumanism, 2024)
This study analyzed scientific output indexed in Scopus regarding environmental impact and indigenous peoples through a bibliometric review of 1,633 documents published between 2003 and 2023. The search was conducted across titles, abstracts, and keywords using a specific search equation. At the same time, the analysis examined the temporal evolution of publications, institutional affiliations, countries of origin, document types, fields of knowledge, publication sources, and keyword co-occurrence. The findings revealed sustained growth in the literature, with a higher concentration in recent years, as well as a predominance of scientific articles and a strong presence within the environmental and social sciences. Production was concentrated primarily in institutions and countries within the Anglophone sphere, while the thematic network was structured around climate change, biodiversity, public health, extractivism, land management, and environmental justice. Collectively, this study enabled the identification of the bibliometric landscape of this field, its primary channels of dissemination, and the lines of research that have guided its development within the recent international scientific literature.